POLYMORPHISM OF CHLOROPLAST DNA REGIONS OF SOME SPECIES FROM SCORPIRIS SPACH SUBGENERA (IRIDACEAE JUSS.) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The information about the research results of the polymorphic regions of chloroplastgenomes of 4 endemic species from Scorpiris subgenera, namely Juno austrotschatkalica Tojibaev,F. Karim, et Turgunov, Juno pseudocapnoides Rukšāns, Juno victoris (F.O. Khass., Khuzhan. andRakhimova) M.B. Crespo, Mart.-Azorín and Mavrodiev and Iris hippolyti (Vved.) Kamelin, ispresented in this article. The research aimed to detect the most variable regions to use for specificprimer design.
Keywords: polymorphizm, plastome, Scorpiris.